Study on Metro Operation Safety Based on a Specific Contact Model for Resilient Wheel - Shuoqiao Zhong; Xin Zhou; Xiaozhen Sheng (Urban Rail Transit)
Abstract Resilient wheel (RW) is gradually promoted for use in China’s subway vehicles recent years, which has been widely used in tram in Europe and China. As measured, the RWs in service on the metro trains have experienced eccentric wear and even polygonization of high order after 30,000 km running. Given that most subway lines have small curve radii, this study assesses the operation safety of vehicle passing through curves with RWs having polygonal wear, as well as their effect on vibration reduction compared to conventional wheels. A numeric simulation model is developed to model the metro vehicle-track dynamic system installed with resilient wheel, where a conventional wheel-rail contact model is modified considering the composite structure of a RW. A RW-rail contact model considering relatively independent motion of the wheel hub and rim is developed, which is integrated into a metro vehicle-track dynamic system model equipped with the RWs. Upon comparing the curving performance of vehicles equipped with conventional wheels, the findings reveal that, in scenarios of surplus-superelevation, the wheel load reduction ratio (WLRR) of conventional wheels demonstrates superior performance. While curving in the case of deficient-superelevation, the WLRR of RWs is lower. Furthermore, the safety performance of the RWs surpasses that of conventional wheels, particularly as the severity of polygonal wear on the wheel increases. These conclusions can be used as a reference for maintenance strategy of the RW applied on metro trains, which is urgently to be built considering the potentially wide promotion of the RW to the subway system.